2001
DOI: 10.1152/ajpheart.2001.281.1.h105
|View full text |Cite
|
Sign up to set email alerts
|

Shear stress regulates occludin content and phosphorylation

Abstract: Previous studies determined that shear stress imposed on bovine aortic endothelial cell (BAEC) monolayers increased the hydraulic conductivity (L(P)); however, the mechanism by which shear stress increases L(P) remains unknown. This study tested the hypothesis that shear stress regulates paracellular transport by altering the expression and phosphorylation state of the tight junction protein occludin. The effect of shear stress on occludin content was examined by Western blot analysis. Ten dyn/cm(2) significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
84
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 111 publications
(93 citation statements)
references
References 34 publications
8
84
1
Order By: Relevance
“…After exposure to SS as described above, SMCs remaining on top of the Matrigel layer were washed twice in PBS with Ca 2Ï© and then lysed with the SDS extraction buffer as outlined by DeMaio et al (8). Lysate was purified from insoluble material by centrifugation at 14,000 g for 10 min, and protein concentrations were determined through the use of a commercially available protein assay (Bio-Rad).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After exposure to SS as described above, SMCs remaining on top of the Matrigel layer were washed twice in PBS with Ca 2Ï© and then lysed with the SDS extraction buffer as outlined by DeMaio et al (8). Lysate was purified from insoluble material by centrifugation at 14,000 g for 10 min, and protein concentrations were determined through the use of a commercially available protein assay (Bio-Rad).…”
Section: Methodsmentioning
confidence: 99%
“…1,6,8,16,36) because, under normal physiological conditions, they are directly exposed to the SS of flowing blood, having a magnitude on the order of 10 dyn/cm 2 (26). It had long been thought that the underlying SMCs were shielded from blood flow and were only subjected to SS when the EC layer was denuded, as in balloon angioplasty, directly exposing SMCs to blood flow SS.…”
mentioning
confidence: 99%
“…In gap junctions, laminar shear stress transiently increases the expression of connexin 43, while disturbed flow sustains the induction of connexin 43 but disorganizes the cell-cell communication [Cowan et al, 1998;Gabriels and Paul, 1998;DePaola et al, 1999]. In tight junctions, shear stress increases occludin phosphorylation and decreases occludin expression, which may be responsible for the increase of hydraulic conductivity of an EC monolayer [DeMaio et al, 2001]. The roles of gap junctions and tight junctions in mechanotransduction during EC migration await further investigation.…”
Section: Cell-cell Adhesions In Shear Stress-induced Ec Migrationmentioning
confidence: 99%
“…Several studies have shown that transvascular exchange can be affected by a change in perfusion rate (14,17,19,32,33,43). A small-pore model has been proposed as a possible mechanism to account for flow-dependent transport of small solutes in cannulated vessels (32); moreover, there have been several recent studies of shearinduced increases in fluid filtration performed in vitro (3,6,37) and in vivo (27,40,41). The mechanism by which shear forces could increase L p appear to be dependent on nitric oxide (NO) (3,15,24).…”
mentioning
confidence: 99%